Kajian eksperimental pemakaian Hidrokarbon Musicool 22 sebagai pengganti R 22 untuk mesin pengatur udara AC split terhadap konsumsi listrik - Wahyu Setiawan; Lukito Dwi Yuono; Kemas Ridhuan; Nurlaila Rajabiah (Universitas Muhammadiyah Metro, 2022)
The use of synthetic refrigerant R22 has been banned by the government which can cause damage to the ozone layer causing global warming effects. temperature (ΔT°C) of the evaporator during the test time at the time of the study. The method used in this research is to vary the refrigerant R 22 and Musicool 22 with a pressure variation of 60,70,80 Psi, the size of the room studied is 3x4x2,5 m and Split AC Changhong, LG, and Panasonic with 1 PK power. Research results it can be seen that each brand of Split AC has a different effect of electricity consumption, the lowest and highest electricity consumption at a pressure of 60 and 80 Psi. Musicool 22 refrigerant is more energy efficient than R22. It can be seen that each brand of Split AC has the effect of the temperature difference (ΔT°C) of the evaporator, which differs the highest at a pressure of 60 and 80 Psi. Musicool 22 refrigerant is more suitable for LG and Changhong brands.